2013
DOI: 10.1212/wnl.0b013e31828cfaa4
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter atrophy distinguishes between Parkinson disease motor subtypes

Abstract: Objective: To assess differences in gray matter (GM) atrophy between 2 Parkinson disease (PD) subtypes: the tremor dominant (TD) subtype and the postural instability gait difficulty (PIGD) subtype.Methods: Patients were classified as belonging to the predominately PIGD (n 5 30) or predominately TD (n 5 29) subtype. Voxel-based morphometry was used to compare GM in these 2 subtypes and to evaluate correlations between predefined regions of interest and the degree of symptoms. In the regions where GM atrophy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
112
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 41 publications
16
112
2
2
Order By: Relevance
“…These observations seem to be consistent with previous studies where cortical thinning was found in motor areas including the left medial SMA and right dorsal pre-SMA without any correlation with UPDRS-III scores or disease duration in those regions (Jubault et al 2011). On the other hand, correlations between cortical gray matter measures in the sensorimotor area and motor symptoms (Lyoo et al 2011;Rosenberg-Katz et al 2013) as well as between cortical thickness in several cortical areas and duration of disease (Lyoo et al 2011;Rosenberg-Katz et al 2013) have been reported in other studies. However, it is unknown whether PD patients had cortical abnormalities in those areas compared to HCs, as those studies did not include control data.…”
Section: Discussionmentioning
confidence: 69%
“…These observations seem to be consistent with previous studies where cortical thinning was found in motor areas including the left medial SMA and right dorsal pre-SMA without any correlation with UPDRS-III scores or disease duration in those regions (Jubault et al 2011). On the other hand, correlations between cortical gray matter measures in the sensorimotor area and motor symptoms (Lyoo et al 2011;Rosenberg-Katz et al 2013) as well as between cortical thickness in several cortical areas and duration of disease (Lyoo et al 2011;Rosenberg-Katz et al 2013) have been reported in other studies. However, it is unknown whether PD patients had cortical abnormalities in those areas compared to HCs, as those studies did not include control data.…”
Section: Discussionmentioning
confidence: 69%
“…However, the involvement of the cerebellum varies between subtypes. Compared with TD, the PIGD subtype exhibits lower GM volumes in the cerebellar culmen and declive [15] and more cholinergic cell loss. Also, the severity of gait and balance disturbance correlates with cholinergic deficits in the cortex and subcortex, including the cerebellum [40].…”
Section: Discussionmentioning
confidence: 99%
“…While a pathological interaction between the BG and the cerebellothalamic circuit (cerebello-thalamo-cortex [CTC] pathway) may play an important role in the genesis of resting tremor [13], gait disturbance in PD may in part be associated with the dysfunction of the prefrontal-subthalamic-pedunculopontine loop [14]. Furthermore, compared with TD, gray matter (GM) is reduced in areas that involve pre- (supplementary motor area), post central gyri, the cerebellar declive, culmen, and the caudate nucleus in PIGD predominate PD patients [15]. Thus, it is reasonable to explore the brain network based on different PD phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients assigned to the TD group had freezing of gait and patients from the PIGD group had noticeable tremor (see supplementary material Table 1). Therefore, we modified and applied stricter criteria on top of the Jankovic-based classification to identify two purer groups, with minimal symptom overlap, referred to here as predominantly-PIGD (p-PIGD) and predominantly-TD (p-TD) [7,8]. To compare subjects with minimal overlapping of motor symptoms, patients were excluded from the TD group if they had a PIGD score [3 or a tremor score \4.…”
Section: Classification Into Pd Subtypesmentioning
confidence: 99%
“…Similarly, patients were excluded from the PIGD group if their tremor score was [3 or their PIGD score was \4. This modified classification has been previously introduced by our group [7,8].…”
Section: Classification Into Pd Subtypesmentioning
confidence: 99%